Characterizing the morphology of somatostatin‐expressing interneurons and their synaptic innervation pattern in the barrel cortex of the GFP‐expressing inhibitory neurons mouse. Issue 2 (24th August 2019) - Zhou, Xiaojuan; Mansori, Ima; Fischer, Tatjana; Witte, Mirko; Staiger, Jochen F.
Abstract: Somatostatin‐expressing (SST+) cells form the second largest subpopulation of neocortical GABAergic neurons that contain diverse subtypes, which participate in layer‐specific cortical circuits. Martinotti cells, as the most abundant subtype of SST+ interneurons, are mainly located in layers II/III and V/VI, and are characterized by dense axonal arborizations in layer I. GFP‐expressing inhibitory neurons (GIN), representing a fraction of mainly upper layer SST+ interneurons in various cortical areas, were recently claimed to include both Martinotti cells and non‐Martinotti cells. This makes it necessary to examine in detail the morphology and synaptic innervation pattern of the GIN cells, in order to better predict their functional implications. In our study, we characterized the neurochemical specificity, somatodendritic morphology, synaptic ultrastructure as well as synaptic innervation pattern of GIN cells in the barrel cortex in a layer‐specific manner. We showed that GIN cells account for 44% of the SST+ interneurons in layer II/III and around 35% in layers IV and Va. There are 29% of GIN cells coexpressing calretinin with 54% in layer II/III, 8% in layer IV, and 13% in layer V. They have diverse somatodendritic configurations and form relatively small synapses across all examined layers. They almost exclusively innervate dendrites of excitatory cells, preferentially targeting distal apical dendrites and apical dendritic tufts of pyramidal neurons in layer I, and rarely target other inhibitory neurons. In summary, our study reveals unique features in terms of the morphology and output of GIN cells, which can help to better understand their diversity and structure–function relationships. Abstract : Using anti‐green fluorescent protein (GFP) immunohistochemistry, biocytin staining and correlative light and electron microscopy, Zhou and colleagues demonstrated that GIN cell boutons (GIN) mainly target the dendrites of pyramidal neurons (dpyr ) at their distal apical dendritic domain in layer I. It indicates that GIN cells in the mouse barrel cortex form rather uniform inhibitory synaptic output although having diverse somatodendritic morphology.